Studi Komparative Pendirian Negara Khilafah Di Indonesia - Indra Utama Tanjung (Universitas Islam Negeri Sumatera Utara, 2018)
This study aims to describe the concept of Caliphate establishment in Indonesia the concept of the Khilafah State offered by Hizb at-Tahrir from various views and perspectives. By using the study of library research, this discourse on khilafah will be compared with various kinds of thoughts. Data collection is done by the method of documentation by retrieving data from existing document documents. The analysis used is content analysis or content analysis. Where data is analyzed based on objectives and the formulation of the problem raised. The conclusion that can be drawn from this study according to the author is that the system of the government Khilafah is not a Shari'a but only a choice, which is the right system to be applied when a government system in its era is a system of kingdoms or sultanates. The Prophet himself never left a definite message on how the system of state administration, for example, how the state was formed, how was the system of appointment of heads of state, who had the right to set laws. Because of this ambiguity it can be seen that the practice of the Islamic state system in its history has always changed.